Power Distance Belief and Consumer Purchase Avoidance: Exploring the Role of Cultural Factors in Retail Dynamics - Lee, Hyejin; Lalwani, Ashok K. (Journal of Marketing Research, 2024)
A common problem faced by contemporary retailers is consumers’ tendency to avoid purchases that postpone or prevent cash flow for retailers, thus negatively affecting retailers’ sales and profits. Little is known about the factors that drive consumers to avoid purchases or about marketing tactics that may reduce the tendency, especially from a cultural perspective. The authors attempt to fill this gap by exploring the role of an important cultural variable, namely, power distance belief (PDB), on consumers’ tendency to avoid purchases. PDB is the extent to which people accept and endorse inequalities in society. A series of 14 studies (including 6 studies in the Web Appendix ) using a variety of operationalizations of the key variables suggest that consumers high (vs. low) in PDB are less likely to avoid purchases (Studies 1a, 1b, and 1c) because they generally perceive greater constraints on their behavior (Study 2). These constraints are aversive, triggering the desire to overcome them and to have more as a compensatory mechanism, thereby reducing the tendency to avoid purchases. Accordingly, low (but not high) PDB consumers’ tendency to forgo purchases is significantly decreased when they perceive greater constraints on their choices and decisions (Study 3) and when they experience a high social density (Study 4). However, high (but not low) PDB consumers’ tendency to avoid purchases significantly increases when individuals perceive that constraints facilitate hierarchy (Study 5) or that constraints lead to positive outcomes (Study 6). Theoretical and managerial implications are discussed.